2002
DOI: 10.1080/10473289.2002.10470843
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Municipal Solid Waste Management on Greenhouse Gas Emissions in the United States

Abstract: Technological advancements, environmental regulations, and emphasis on resource conservation and recovery have greatly reduced the environmental impacts of municipal solid waste (MSW) management, including emissions of greenhouse gases (GHGs). This study was conducted using a life-cycle methodology to track changes in GHG emissions during the past 25 years from the management of MSW in the United States. For the baseline year of 1974, MSW management consisted of limited recycling, combustion without energy rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 2 publications
2
49
0
8
Order By: Relevance
“…Methane emission (in CO 2 eq) from landfill is accounted for over 96% of total emission in waste management as shown in Table 3. This results were in accordance with literature (Chen & Lin 2008;Weitz et al 2002) which has found out that, the net GHG emissions for a given material was the lowest for source reduction and the highest for landfilling. Hence, the authors wish to present the significance of the methane emission from landfill and thus promote diversion of compostable material from the waste stream.…”
Section: Emissions From Sow Composting Activitysupporting
confidence: 82%
“…Methane emission (in CO 2 eq) from landfill is accounted for over 96% of total emission in waste management as shown in Table 3. This results were in accordance with literature (Chen & Lin 2008;Weitz et al 2002) which has found out that, the net GHG emissions for a given material was the lowest for source reduction and the highest for landfilling. Hence, the authors wish to present the significance of the methane emission from landfill and thus promote diversion of compostable material from the waste stream.…”
Section: Emissions From Sow Composting Activitysupporting
confidence: 82%
“…Segundo Thorneloe et al (2002), o aproveitamento desses gases representa uma opção potencial para redução das emissões de GEE, além de ter ligações com outros setores que somam oportunidades de redução na emissão de GEE. Com o intuito de contribuir para a solução da problemática apresentada, propôs-se estudar a implementação de um projeto MDL numa estação de tratamento de esgoto (ETE), mais especificamente o estudo de caso da ETE Brasília Norte, por meio de mínimas modificações e da otimização de parâmetros operacionais.…”
Section: Nos Sites Do United Nations Framework Convention On Climateunclassified
“…The U.S. communities' actions, such as technological advancements, environmental regulations, and emphasis on resource conservation and recovery, have significantly reduced the environmental impacts of municipal solid waste, including greenhouse gas emissions [7]. However, neither the solid waste generation nor the recycling rate is decreasing.…”
Section: Introductionmentioning
confidence: 99%